Cybersecurity Awareness among College Students in Libyan Universities last (Faculty of Education Scientific Journal, 2025)
Cybersecurity threat continues to be a growing concern worldwide in recent times. This could be related to the digital revolution that has turned the internet into a breeding ground for cybercriminals. The growing number of cybercrimes emphasizes the importance of raising awareness and providing education on cybersecurity for individuals and businesses. This study explores the influence of password security, cybersecurity knowledge, and self- perception of skill on awareness of cybersecurity among university students in Libya. Questionnaire collected from 480 college students. Smart PLS-SEM 3.3.9 used to analyze the data collected. The findings indicated a positive and significant association of password security, cybersecurity knowledge, and self-perception of skill on awareness of cybersecurity. This research suggests that there should be increased focus on educating the general public, particularly students, about ethical internet practices and cybersecurity. Moreover, the primary focus of the research highlighted the importance of increasing cybersecurity education for the students.
Keywords: Cybersecurity Awareness; Libyan university; Cybercrime; information security